Saving students money with ebooks: A cross-departmental collaboration between interlibrary loan and course reserve. Issue 4 (1st October 2016) - Riha, Emily C.; LeMay, Danika
Abstract : At the University of Minnesota Libraries, the interlibrary loan, acquisitions, and course reserve departments developed a new, data-driven project to provide students access to required course materials through patron-driven acquisition and cross-departmental collaboration. Item usage and student cost-savings data were collected throughout the project. During the spring 2015 semester, a survey was distributed to students across various disciplines affected by the project. Intended to measure the pilot project's success, the data and survey also yielded compelling evidence that academic libraries can best serve student needs by purchasing multiple user ebooks of required materials and promoting their availability.